New Borders and New Spaces: The Case of Theasylum Seeker in Strasbourg, France - Zander, Patricia (Quaestiones Geographicae, 2010)
The need for borders seems an old-fashioned notion, especially when we consider the border in its most basic sense: as a barrier and a filter. Within the European Union, the idea of the disappearing border is underlined when we see its physical signs such as buildings and checkpoints fall out of use or disappear. We submit here that due to the complex interplay between supra-national, national and local structures today, the notion of the border has instead evolved and become less visible, but very present, and very complex. When we examine the particular case of the asylum seeker in Strasbourg, France, we see that even in this ‘borderless’ city administrative mechanisms keep him ‘out’, even when he is physically in our midst, by creating ‘non-spaces’, or by manipulating his use of time and everyday spaces so that he cannot anchor himself.